2017
DOI: 10.1155/2017/2061260
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Time Series Model for Predicting Jute Yarn Demand: Case Study

Abstract: In today's competitive environment, predicting sales for upcoming periods at right quantity is very crucial for ensuring product availability as well as improving customer satisfaction. This paper develops a model to identify the most appropriate method for prediction based on the least values of forecasting errors. Necessary sales data of jute yarn were collected from a jute product manufacturer industry in Bangladesh, namely, Akij Jute Mills, Akij Group Ltd., in Noapara, Jessore. Time series plot of demand d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 13 publications
0
11
0
2
Order By: Relevance
“…The triple exponential smoothing method is used when the data shows seasonal trends and behavior [11]. Triple exponential smoothing method is done by using the equation: In forecasting, several methods are applied together, to find the best method in the selection of criteria used by reference to determine the best model [5]. In the forecasting process, whether or not the model used is very influential in the decisions made.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The triple exponential smoothing method is used when the data shows seasonal trends and behavior [11]. Triple exponential smoothing method is done by using the equation: In forecasting, several methods are applied together, to find the best method in the selection of criteria used by reference to determine the best model [5]. In the forecasting process, whether or not the model used is very influential in the decisions made.…”
Section: Methodsmentioning
confidence: 99%
“…In forecasting, several methods are applied together, to find the best method in the selection of criteria used by reference to determine the best model [5]. In the forecasting process, whether or not the model used is very influential in the decisions made.…”
Section: Introductionmentioning
confidence: 99%
“…The values of MAPE, MAD, and MSE decreased along with increasing smoothing constant value. Research showed that minimum error occurred at constant optimal smoothing ( α = 0.9) which resulted in MAPE of 13.1, MAD of 117.4, and MSD of 26,912.1 ( Karmaker, Halder & Sarker, 2017 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Prediksi produk yang sepatutnya memainkan peranan penting dalam mengurangi persediaan yang tidak perlu dan merapikan masalah perencanaan yang mengakibatkan peningkatan laba [4]. Saat ini konsep sistem pendukung keputusan untuk berbasis komputer berkembang dan banyak metode yang sangat cepat dapat digunakan untuk membantu proses pengambilan keputusan dengan melakukan pendekatan sistematis [5].…”
Section: Pendahuluanunclassified